The study on heat distribution inside the combustion chamber of a gas fired pyrolysis system - Ahmad Zulfadzli, Ahmad Murad (2010)
The ability of lignocelluloses materials to pyrolyze into bio-fuel depends on the amount of heat transferred supply to the biomass feed.Typically,by using fixed bed pyrolysis system,heat is supplied through the reactor wall.In this research,the effects of heat distribution inside the combustion chamber of direct fired pyrolysis system is studied to look the effectiveness heat transfer process from gas burner to the reactor.The experiment of different setting of fuel and air of gas burner was done.The settings are 16 mbar of fuel with 2.5 of air,16 mbar of fuel with 5 of air,16 mbar of fuel with 7.5 of air,19 mbar of fuel with 2.5 of air, 19 mbar of fuel with 5 of air,and 19 mbar of fuel with 7.5 of air.The temperatures distributions of the furnace were investigated.The different type of the setting of fuel and air for gas burner will influence the heat distribution in the gas fired pyrolysis system.The results of the heat distribution of the furnace show similar pattern for 6 different setting but the temperature value were different.The best setting of fuel and air was gained by selecting the shortest time of the setting to reach 400 ºC of the temperature of the reactor.The 400 ºC is the temperature of pyrolysis process started.It was found that the best setting of fuel and air for gas burner is the setting of 19 mbar of fuel with 2.5 of air.The time taken to achieve pyrolysis temperature from the best setting is 25 minutes.The heat distribution patterns also have been reviewed and discussed in this research.This study provides clearer insight into the heat distribution of the gas fired pyrolysis system.